Mean performance of parents and hybrids for yield and related traits in bottle gourd [Lagenaria siceraria (Mol.) Standl.] - Kumar, Virendra; Kumar, Anil; Ram, C. N.; Singh, R. B.; Jha, Aastik; Singh, Ashish Kumar; Upahdyay, D. K.; Narayan, Raj (Journal of Neonatal Surgery, 2025)
This study investigates the mean performance for yield and quality traits in bottle gourd (Lagenaria siceraria (Mol.) Standl.) using a half-diallel mating design involving nine diverse genotypes, which produced 36 F₁ hybrids evaluated over two Zaid seasons (2024 & 2025) in a randomized complete block design with three replications. Significant genotypic variance was observed across 20 traits, encompassing yield and quality parameters. Parental lines displayed distinct strengths: Pant Lauki-3 (P6) recorded the highest fruit yield (4.81 kg/plant), Kashi Ganga (P7) excelled in fruit weight (1.08 kg) and Arka Bahar (P8) exhibited the highest dry matter content (6.19%). Among hybrids, P2 × P5 emerged as the top performer with a yield of 6.65 kg/plant, showing 45.1% heterosis over the better parent. Notable recombinants included P6 × P9 (longest fruits and high yield), P1 × P7 (highest TSS and reducing sugars) and P3 × P6 (earliest harvest and highest dry matter). Biochemical analysis revealed strong hybrid advantages, with P6 × P7 accumulating the highest reducing sugars (2.32%) and P1 × P6 leading in non-reducing sugars (1.12%). Genetic analysis indicated additive gene action for vine length and fruit number, while non-additive effects predominated in yield heterosis. Crosses P2 × P5, P1 × P8, and P6 × P9 are recommended for commercial cultivation due to their superior yield, early maturity and enhanced nutritional quality, offering a promising foundation for breeding elite bottle gourd.